(untitled) (Ameghiniana, 2014)
The present paper deals with the description of the first remains of the Family Mesotheriidae in the Quebrada Fiera locality. The fauna from Quebrada Fiera comes from sediments nowadays considered to represent the base of the Agua de la Piedra Formation. The recovered faunal assemblage includes typical elements of the Deseadan Age (late Oligocene), shared with both Patagonian and lower latitude associations (e.g., Salla, Bolivia). A unique specimen of Mesotheriidae has been recovered after several field seasons since 2006. It is a palatal portion in two fragments, one bearing the I1 and the other with left P4-M2 and right M1-2. Morfological and metrical features of this material reveal a taxon much closer to the Patagonian mesotheriid species Trachytherus spegazzinianus than to the Bolivian taxa, T. alloxus and T. subandinus, and it is determined as Trachytherus cf. T. spegazzinianus. Its presence in Mendoza fills a gap in the expected geographical distribution of this mesotheriid, as it was also recorded in the Bolivian site of Lacayani. The scanty record of mesotheriids in Quebrada Fiera contrasts with Salla and Patagonian localities.